"Technological Determinants of Jordanian Public Universities’ Intention to Adopt E-Government: The Moderating Role of Awareness (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
E-government is given a lot of weight in the evolution of global information and governance systems. Notwithstanding Jordan’s persistent efforts to promote better public services through the use of e-government, the country’s citizen adoption rate is actually quite low. This emphasizes how critical it is to determine the obstacles keeping people from adopting these easily accessible e-services. The current study examines the relationship between technology factors (relative advantage, compatibility, and complexity) and intention to use e-government. Furthermore, the moderating effect of awareness is also examined. Data were collected from ten public universities in Jordan through a survey questionnaire, which was distributed to 400 lecturers and administrative staff using a stratified random sampling technique. A total of 379 valid responses were received, representing a response rate of approximately 94%. The Smart PLS tool was used to analyse the data. The results revealed that relative advantage and compatibility are strongly associated with intention to use e-government. Similarly, only one of the three indirect effect hypotheses was supported, indicating that awareness moderates the relationship between relative advantage, compatibility, and intention to use e-government. Accordingly, Jordanian public universities should invest in improving their technical infrastructure and maintaining robust cybersecurity to ensure safe and dependable e-government systems. Additionally, implementing targeted training and awareness campaigns will enhance digital literacy, encourage active user engagement, and reduce resistance to change
Keywords: E-Government; Relative Advantage; Compatibility; Complexity; Intention to Use; Jordan